English Pronunciation Errors Made by Torajan Speakers of English (TSE) - Linerda Tulak Tondok (UKI TORAJA, 2016)
This research was aimed to find out (i) the pronunciation errors and (ii) the causalfactors of pronunciation errors made by the students of UKI Toraja as Torajan speakersof English. The researcher employed a descriptive qualitative method. The subjectswere ten students and taken by using random purposive sampling. Data were takenfrom the recording of students’ pronunciation when telling a chosen topic andinterview, then analyzing by error analysis. The result showed that, (i) Errors inconsonants were sounds [f, v, ð, ?, z, ?, ?, t?,] omission medial [j], omission of final[t,d,k]. Then errors in vowels were sound [i:,?,e,æ,?,??,??,?:,??,e?]. (ii) the causal factorsof making pronunciation errors were language transfer, overgeneralization, ignoranceof rule restrictions, incomplete in applying rules, and false concept hypothesized;modality; age; and universal hierarchy of difficulty. Then, additional data frominterview showed that the students made pronunciation errors caused by the lack ofopportunity to use English in their daily lives, the neglect of the pronunciation’simportance, and the lack of practice in imitating the kind of English sounds.